Penerapan Cerita Rakyat Dalam Meningkatkan Keterampilan Menulis Pada Pembelajaran Bahasa Indonesia Sebagai Wujud Cinta Budaya Bangsa - Meliana Br Gultom; Marasi Parningotan Siagian, Yosua; Ronaldus Silalahi , Hizkia; Sembiring, Rina; Munthe, Dea; Christina, Loise (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Folklore is one of the nation's cultural heritages that contains moral, social, and cultural values which can be utilized as a learning medium in Indonesian language education. The use of folklore in the learning process aims not only to improve students' language skills but also to foster a sense of love for the nation's culture. This article aims to describe the implementation of folklore in improving writing skills in Indonesian language learning as a manifestation of love for the nation's culture. The method employed in this study is a library research approach by reviewing various relevant sources, including scientific journals, books, and scholarly articles related to folklore-based learning, writing skills, and culture-based character education. The findings indicate that the implementation of folklore in the learning process can enhance students' ability to develop ideas, organize written texts, enrich vocabulary, and improve writing creativity. Furthermore, folklore plays an important role in instilling character values, strengthening national identity, and fostering appreciation and love for the nation's cultural heritage. Therefore, folklore can serve as an effective alternative learning medium to improve writing skills while simultaneously developing students' cultural awareness and character.